2023
DOI: 10.3390/ijerph20054400
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Sustainable Engineering with PjBL during the COVID-19 Pandemic

Abstract: Sustainable Engineering education must provide cyber-physical and distributed systems competencies, such as the Internet of Things (IoT), to contribute to the Sustainable Development Goals (SDG). The COVID-19 pandemic caused profound impacts arising from a traditional on-site teaching model rupture and demanded distance learning for engineering students. In this context, we considered the following Research Questions (RQ): How can Project Based Learning (PjBL) be applied in hardware and software courses from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 30 publications
(40 reference statements)
0
5
0
Order By: Relevance
“…The length of the studies indicated in the articles differed too: while some studies included online PBL as part of a semester course typically lasting 14-16 weeks, some only referred to the actual length of the implementation of online PBL (6-8 weeks). Hayashi et al (2023) reported on several courses implemented over the academic year 2020-2021. The remaining characteristics of studies are provided in Table 4 in Appendix C.…”
Section: General Information On the Studies Reviewedmentioning
confidence: 99%
See 4 more Smart Citations
“…The length of the studies indicated in the articles differed too: while some studies included online PBL as part of a semester course typically lasting 14-16 weeks, some only referred to the actual length of the implementation of online PBL (6-8 weeks). Hayashi et al (2023) reported on several courses implemented over the academic year 2020-2021. The remaining characteristics of studies are provided in Table 4 in Appendix C.…”
Section: General Information On the Studies Reviewedmentioning
confidence: 99%
“…Second, some studies also referred to discipline-related specific tools, software, and applications or generic tools that were used to implement the content of the projects. Examples of this type included visualizations tools such as Java, Tableau, D3 (Beyer et al, 2021), Internet of Things (IoT) technologies (Baudin et al, 2022;Hayashi et al, 2023); Azure Notebooks (used for remote programming; Sakamaki et al, 2022), a virtual desktop infrastructure enabled by Citrix machine creation system which enables instructors to take control of students' virtual machines (Sola-Guirado et al, 2022), making use of the online virtual simulation experiment websites, employing bioinformatics tools (VSEARCH and MicrobiomeAnalyst) in order to analyze data (Sun et al, 2023), and the use of online platforms for creating multimedia videos or multimodal content (Canva and Powtoon; Poonpon, 2021).…”
Section: Software Used In the Implementation Of Online Pblmentioning
confidence: 99%
See 3 more Smart Citations